Different perspectives on the reception and appropriation of Piagetian ideas in the Brazilian context (Memorandum: Memória e História em Psicologia, 2024)
The recently released book The transnational legacy of Jean Piaget: a view from the 21st century, published by Springer Nature, aims to internationally disseminate the studies carried out by the Helena Antipoff Documentation and Research Center (CDPHA) at the Federal University of Minas Gerais. Organized and edited by Regina Helena de Freitas Campos and Erika Lourenço (UFMG), in partnership with Marc J. Ratcliff (Université de Genève), the book has 19 chapters that explore various aspects of Piaget's influence. Among the topics covered, the following stand out: the clinical method for monitoring and intervening in the demands of children and adolescents; the historical-critical method for analyzing the interaction between internal and external factors in the History of Science; the right to education as a basis for intellectual and moral development; the promotion of peace; and multiculturalism as a tool for facilitating communication between different perspectives.